A Heterobimetallic 2-D Coordination Polymer [Na2(Cu2I2(2pyCOO)4)(H2O)4]n (2pyCOO - Kamari, Anis A.; Haque, Rosenani A.; Razali, Mohd Rizal (MDPI, 2016)
A heterobimetallic 2-D coordination polymer, [Na2(Cu2I2(2pyCOO)4)(H2O)4]n (1) (2pyCOO=picolinate) was synthesized and characterized. The complex was also structurally characterized using single X-ray diffraction studies that revealed the complex 1 having a vertex symbol of 4.82 which corresponds to fes topology. Together with hydrogen bonds and interdigitating n...n interactions, these thus facilitate the formation of 3-D supramolecular network. The nitrogen gas absorption amount of 1 at 77 K shows a small volume of N2 sorption isotherm with a small Langmuir and a Brunauer-Emmett-Teller (BET) surface area indicating that the heterobimetallic 3-D supramolecular of 1 exhibits a very weak ability of adsorbing gas.